2020
DOI: 10.1108/ijesm-09-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural resources extraction on energy consumption and carbon dioxide emission in Ghana

Abstract: Purpose Even though many studies have attempted to understand the drivers of carbon dioxide emission and energy consumption to help tackle environmental issues, not much has been done to estimate the effect of natural resources extraction on these two variables. This paper aims to analyze the long-run and short-run carbon dioxide emission and energy consumption effect of natural resources extraction in Ghana. Design/methodology/approach The theoretical foundation for this study is the Stochastic Impacts Regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 57 publications
10
59
1
Order By: Relevance
“…In line with Kwakwa et al (2018), natural resources had a (1) significant positive impact on carbon emissions under the fixed and pooled OLS and (2) a non-significant positive effect on carbon emissions under the random and FMOLS. Consistent with theoretical predictions, trade openness' positive impact on carbon emissions was significant under the random and pooled OLS and non-significant under the fixed and FMOLS.…”
Section: Data Analysis Discussion and Intepretationsupporting
confidence: 55%
“…In line with Kwakwa et al (2018), natural resources had a (1) significant positive impact on carbon emissions under the fixed and pooled OLS and (2) a non-significant positive effect on carbon emissions under the random and FMOLS. Consistent with theoretical predictions, trade openness' positive impact on carbon emissions was significant under the random and pooled OLS and non-significant under the fixed and FMOLS.…”
Section: Data Analysis Discussion and Intepretationsupporting
confidence: 55%
“…However, the findings of these studies are mostly contradictory and unsettled across various methodological frameworks and countries scrutinised. While some works concluded that trade openness brings about improvement in environmental quality through various channels (Aichele & Felbermayr, 2013;Zerbo, 2015;Kwakwa, Alhassan & Adu, 2018;Li, Xu & Yuan, 2015;Shahbaz, Tiwari & Nasir, 2013c;Wan, Nakada & Takarada, 2018;Dogan and Seker, 2016;Ling, Ahmed, Muhamad & Shahbaz, 2015;Hasson & Masih, 2017;Jabeen, 2015;Cherniwchan, 2017;Dogan and Turkekul, 2016;Destek, Balli & Manga, 2016;Zerbo, 2017;Roy, 2017), a few studies contended that trade openness results in worsening environmental condition (Twerefou, Appiah-Konadu & Anaman, 2015;Jamel & Maktouf, 2017;Raza & Shah, 2018;Le, Chang & Park, 2016;Balin, Akan & Altayligil, 2017;Lin, 2017;Solarin, Al-Mulali, Musah, & Ozturk, 2017;Shahbaz, Nasreen, Ahmed & Hammoudeh, 2017;Fernández-Amador, Francois, Oberdabernig & Tomberger, 2017;Kebede, 2017). On the contrary, another group of works found robust evidence that trade openness has no impact on the environment (Gale and Mendez, 1998;Oh and Bhuyan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argue that natural resource extraction or consumption through mining, agriculture, non-renewable can benefit the environmental. However, (Bekun et al, 2019;Kwakwa, Alhassan, & Adu, 2019) conclude there is a negative impact of natural resources on the environment. According to Kwakwa, Alhassan, and Adu (2019) They argue that natural resources abundance promotes higher economic development which induces serious environmental concerns.…”
Section: Literature Reviewmentioning
confidence: 99%